Unraveling the regulation of pyocyanin synthesis by RsmA through MvaU and RpoS in Pseudomonas aeruginosa ID4365. (7th October 2022) - Montelongo‐Martínez, Luis F.; Hernández‐Méndez, Cristina; Muriel‐Millan, Luis F.; Hernández‐Estrada, René; Fabian‐Del Olmo, Misael J.; González‐Valdez, Abigail; Soberón‐Chávez, Gloria; Cocotl‐Yañez, Miguel
Abstract: Pyocyanin is a phenazine with redox activity produced by Pseudomonas aeruginosa that is harmful to other bacteria and eukaryotic organisms by generating reactive oxygen species. Gene regulation of pyocyanin synthesis has been addressed in the PAO1 and PA14 strains and involves the three‐quorum sensing systems Las, Rhl, and Pqs; the regulators RsaL, MvaU, and RpoS, and the posttranscriptional Rsm system, among others. Here, we determined how RsmA regulates pyocyanin synthesis in P. aeruginosa ID4365, an overproducer strain. We found that, in the protease peptone glucose ammonium salts medium, rsmA inactivation increases pyocyanin production compared with the wild‐type strains ID4365, PAO, and PA14. We showed that RsmA regulates inversely the expression of both phz operons involved in pyocyanin synthesis; particularly the phz2 operon is positively regulated at the transcriptional level indirectly through MvaU. In addition, we found that the phz1 operon contributes mainly to pyocyanin synthesis and that RsmA negatively regulates phzM and phzS expression. Finally, we showed that translation of the sigma factor RpoS is positively regulated by RsmA, and the expression of rpoS under an independent promoter decreases pyocyanin production in the IDrsmA strain. These results indicate that RsmA regulates not only the genes for pyocyanin production but also their regulators.